PEMANFAATAN OBAT BUFFER STOCK NASIONAL DI INSTALASI FARMASI KABUPATEN/KOTA DAERAH ISTIMEWA YOGYAKARTA TAHUN 2007, 2008, DAN 2009 - , Meiza Apsari; , Prof.Dr.Dra.Sri Suryawati,Apt ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. In term of fulfilling the necessity of public health service, to prevent the medicine unavailability (stock out) and the continuously shortage number of medicineâs supply, Pharmacy Installation of City/County provides buffer stock medicine. Purpose. To find out the usage of national buffer stock medicine in IFK starting from the availability of national buffer stock medicine, to observe the endeavor of national buffer stock medicine usage and to collect experience on implementation of national buffer stock medicine in IFK of Special Region of Yogyakarta. Method. It used analytic â descriptive method in retrospectively data collecting. Data was obtained from observation and in depth interview in Pharmacy Installation of Health Service in City/County of Special Region of Yogyakarta. Finding. The usage of buffer stock medicine in IFK of Special Region of Yogyakarta to fulfill the necessity and support the flow of public health service in local public health centers, IFK continuously conducted evaluation and supervisory the medicine necessity in each basic health service. If there was a medicine shortage, it would make a deal with other IFK in Special Region of Yogyakarta to borrow the medicine or made a coordination with Provincial Pharmacy Installation. Nonetheless, as the medicine was oversupply and the medicineâs condition was closed to expired date, IFK would optimize the usage by offering to local public health centers. Conclusion. The availability of national buffer stock medicine in Pharmacy Installation of City/County of Special Region of Yogyakarta in 2007, 2008, and 2009 by the program of fulfilling medicine availability was good. The usage of national buffer stock medicine in Pharmacy Installation of City/County of Special Region of Yogyakarta comprised of a better planning in 5 County/City, the medicine procurement based on demand, type fitness and number of medicine had not been better yet, the quality control was good, except in 2007, what happened in Bantul Regency was poor, storage facility (rack/pallet) was as standard, supporting facility for moisture was as standard, storage system of FIFO/FEFO, medicine usage frequency had slow moving and fast moving medicine, expired medicine in Bantul Regency in 2007 was 12% and in 2008 was 21%. The experience in implementing national buffer stock medicine was that Pharmacy Installation of Yogyakarta City still needed national buffer stock medicine, while Pharmacy Installation in Regency of Bantul, Gunungkidul, Kulonprogo and Sleman was more preferred in fulfilling medicine necessity via budget of Special Allocation Fund (DAK).